Beckman Model PC-352 Process Chromatograph programmer and analyzer
Beckman Instruments entered the gas chromatograph business in 1956 with the acquisition of the successful Watts Manufacturing Company. Later that year, Beckman Instruments produced its first gas chromatograph, the GC-1, which was intended for laboratory use. Shortly after, Beckman Instruments produced a line of gas chromatographs for industrial use, which offered both automation and customization. These instruments were used by the petroleum industry and in the fight against air pollution.
Keywords: Scientific apparatus and instruments; Gas chromatography; Gas chromatography--Instruments; Beckman Instruments, Inc.